2020
DOI: 10.3390/pathogens9030207
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sulfadoxine–Pyrimethamine for Intermittent Preventive Treatment of Malaria and Adverse Birth Outcomes in Pregnant Women

Abstract: Effectiveness of intermittent preventive treatment in pregnancy with sulfadoxine–pyrimethamine (IPTp-SP) for prevention of malaria and adverse birth outcomes can be compromised by parasites-resistance to sulfadoxine–pyrimethamine. This study prospectively evaluated the effectiveness of IPTp-SP in Southeast Tanzania. From January 2017 to May 2019, HIV-negative and malaria-negative (mRDT) pregnant women attending their first antenatal-care visit in the second or third trimester (n = 500) were enrolled to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
3
10
1
Order By: Relevance
“…is conforms with several studies conducted in Tanzania [44,45], Cameroon [46], Nigeria [47], and Ghana [48].…”
Section: Discussionsupporting
confidence: 92%
“…is conforms with several studies conducted in Tanzania [44,45], Cameroon [46], Nigeria [47], and Ghana [48].…”
Section: Discussionsupporting
confidence: 92%
“…We found that more than 3 doses of SP/IPTp signi cantly reduced the odds of LBW. This is in conformity with several studies conducted in Tanzania (41,42), Cameroon (43), Nigeria (44) and Ghana (45). The protective nature of SP against LBW could be explained by its therapeutic effect against both malaria and non-malaria infections.…”
Section: Discussionsupporting
confidence: 91%
“…This replaces the original recommendation of two doses of SP, following substantial data that demonstrated reduced risk of preterm birth and LBW as well as improved birth weight when three or more courses were administered (68)(69)(70). In mathematical modeling studies, it was estimated that three or more doses of IPTp-SP uptake would lead to a 30% relative reduction in LBW occurrence (70)(71)(72)(73).…”
Section: Insecticide-treated Nets Indoor Residual Spraying and Intementioning
confidence: 99%